(untitled) (Revista revoluciones, 2021)
MiPymes have become one of the largest sources of economic movement in the country, however, their mortality rate is high because they do not last for a long time and do not develop with should be, that is why in the This project intends to carry out an analysis on the impact that a financial department has to promote the development of MiPym in the city of Machala. For this, a quantitative method investigation was carried out, with a descriptive-experimental scope, where a survey was presented aimed at company managers, to confirm their opinion about this influence. With the information it was possible to consider that financial management is necessary to establish decision-making and know its financial status, taking into account a vertical balance analysis that allows it to be compared with the financing of other companies